2015
DOI: 10.1002/ejsp.2100
|View full text |Cite
|
Sign up to set email alerts
|

That is how we do it around here: Levels of identification, masculine honor, and social activism against organized crime in the south of Italy

Abstract: Masculine honor is an important cultural code in the south of Italy. Italian criminal organizations (COs) manipulate and exploit this code to maintain legitimacy among local populations and exert social control in the territory where they operate. This research tested the hypothesis that different levels of identification-the region and the nation-would have opposite associations with male honor-related values and, indirectly, with intentions to oppose COs collectively. Results from a sample of young southern … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(49 citation statements)
references
References 39 publications
5
44
0
Order By: Relevance
“…This in turn exerted a negative indirect effect of regional identity on intentions to oppose COs collectively. Thus, in line with Travaglino, et al (2015) and ICAT we also predict a negative indirect effect of regional identity via masculine honour ideology on collective action intentions (H3b). These two contrasting routes from identity to collective action intentions are tested in the present study.…”
Section: Honour Codes and Social Changesupporting
confidence: 70%
See 4 more Smart Citations
“…This in turn exerted a negative indirect effect of regional identity on intentions to oppose COs collectively. Thus, in line with Travaglino, et al (2015) and ICAT we also predict a negative indirect effect of regional identity via masculine honour ideology on collective action intentions (H3b). These two contrasting routes from identity to collective action intentions are tested in the present study.…”
Section: Honour Codes and Social Changesupporting
confidence: 70%
“…Abrams and Grant (2012) hypothesised and found that the more strongly people identified with their groups the more likely they were to advocate the pursuit of radical change to advance the group's interest. In apparent contrast, Travaglino et al (2015) demonstrated that individuals' identification with a Southern…”
Section: Identity Social Change Beliefs and Masculine Honourmentioning
confidence: 92%
See 3 more Smart Citations